2017
DOI: 10.1371/journal.pgen.1007104
|View full text |Cite
|
Sign up to set email alerts
|

A case-control collapsing analysis identifies epilepsy genes implicated in trio sequencing studies focused on de novo mutations

Abstract: Trio exome sequencing has been successful in identifying genes with de novo mutations (DNMs) causing epileptic encephalopathy (EE) and other neurodevelopmental disorders. Here, we evaluate how well a case-control collapsing analysis recovers genes causing dominant forms of EE originally implicated by DNM analysis. We performed a genome-wide search for an enrichment of "qualifying variants" in protein-coding genes in 488 unrelated cases compared to 12,151 unrelated controls. These "qualifying variants" were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
(35 reference statements)
0
26
0
Order By: Relevance
“…This study provided the initial evidence of the deleterious effect of variants p.Ser347Arg, p.Thr374Ile, and p.Gly379Arg on KCNB1 function. Following the initial identification of KCNB1 variants (Torkamani et al, ), 29 new KCNB1 variants have been reported in 37 patients detected through next‐generation high‐throughput sequencing in cohorts of individuals with developmental delay and/or DEE (Allen et al, ; Fitzgerald et al, ; Saitsu et al, ; Soden et al, ; Srivastava et al, ; Thiffault et al, ; Torkamani et al, ; Calhoun, Vanoye, Kok, George, & Kearney, ; de Kovel et al, ; Latypova et al, ; Marini et al, ; Miao, Peng, Chen, Gai, & Yin, , 2018; Parrini et al, ; Samanta, ; Zhu et al, ). The majority of these patients had epilepsy, intellectual disability, and behavioral problems (MIM# 616056; epileptic encephalopathy, early infantile, 26).…”
Section: Introductionmentioning
confidence: 99%
“…This study provided the initial evidence of the deleterious effect of variants p.Ser347Arg, p.Thr374Ile, and p.Gly379Arg on KCNB1 function. Following the initial identification of KCNB1 variants (Torkamani et al, ), 29 new KCNB1 variants have been reported in 37 patients detected through next‐generation high‐throughput sequencing in cohorts of individuals with developmental delay and/or DEE (Allen et al, ; Fitzgerald et al, ; Saitsu et al, ; Soden et al, ; Srivastava et al, ; Thiffault et al, ; Torkamani et al, ; Calhoun, Vanoye, Kok, George, & Kearney, ; de Kovel et al, ; Latypova et al, ; Marini et al, ; Miao, Peng, Chen, Gai, & Yin, , 2018; Parrini et al, ; Samanta, ; Zhu et al, ). The majority of these patients had epilepsy, intellectual disability, and behavioral problems (MIM# 616056; epileptic encephalopathy, early infantile, 26).…”
Section: Introductionmentioning
confidence: 99%
“…We focus on EPI because this disorder had DN and CC data, including recent rare CC variant studies 12,13 . In addition, multiple EPI genes were prioritized by gTADA.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, additional risk genes have been reported by meta-analyzing DNMs and rare case-control (CC) variants, an approach that has been particularly successful for autism spectrum disorders (ASD) 9,10 . For epilepsy (EPI), multiple associated genes have been identified through DN based studies 4,5,11 , and in recent years, a number of EPI significant genes have also been identified through CC studies 12,13 . We hypothesized that, as for ASD, additional significant EPI genes could be discovered through the integration of DN and CC data.…”
Section: Introductionmentioning
confidence: 99%
“…Here we investigate using LIMBR in this role. Using a cohort of 488 epileptic encephalopathy-affected case subjects and 12,151 unrelated control subjects from a previous rare variant collapsing analysis, 27 we performed a group-wise association test on the five epilepsy-associated genes mentioned above (Equation 4). 17 In the first set of tests, we assign equal weights to all variants; in the second, we weight the variants by the inverse percentile of their exon-level intolerance scores (details in Material and Methods).…”
Section: Using Sub-region Level Intolerance In Analyses Of Whether Thmentioning
confidence: 99%